The Effect of Value Congruity, Customer Brand Engagement, Consumer Brand Identification, and Affective Brand Commitment on Brand Loyalty of Roughneck Products 1991 - Muhammad Ichsan; Ana Noor Andriana Ana Noor Andriana (Al-Makki Publisher, 2023)
This study aims to determine the effect of value congruity, customer brand engagement, customer brand identification and affective commitment simultaneously and partially on customer loyalty of Roughneck 1991 products. The variables used in this study consist of independent variables, namely value congruity, (X1) customer brand engagement (X2), customer brand identification (X3) and affective commitment (X4) and the dependent variable namely brand loyalty (Y). The analysis method uses quantitative methods. The population of this study was consumers aged 10-41 years who purchased local Roughneck products 1991 with a sample of 100 respondents. This study used purposive sampling method. Data collection techniques for literature research, internet research, and field research in the form of interviews, observations, and questionnaires. The results of this study show that the results of the F Test calculation (simultaneous) show that the variables value congruity, customer brand engagement, customer brand identification and affective brand commitment together (simultaneously) have a significant effect on brand loyalty, and from the results of the analysis Test t (partial) shows that partially the variables value congruity, customer brand engagement, customer brand identification and affective brand commitment have a significant effect on brand loyalty.